A Rare Prenatal Case: Greig Cephalopolysyndactyly Syndrome - Tilbe Hakçıl; Gülsüm Kayhan; Tuncay Nas; Pınar Telli Celtemen; Meral Yirmibeş Karaoğuz (Gazi Medical Journal)
Greig cephalopolysyndactyly syndrome (GCPS) is a rare genetic disorder characterized by macrocephaly, prominent forehead, hypertelorism, preaxial and/or postaxial polydactyly, and cutaneous syndactyly. Mutations that cause haploinsufficiency in the zinc finger protein family member 3 (GLI3) gene, which is located on the short (p) arm p14 region of chromosome 7 (Chr.7), have been associated with this syndrome. Here, a case of prenatal GCPS with haploinsufficiency of the GLI3 gene is presented. A 32-year-old woman, in her 21st week of the first pregnancy, was referred to our center for cytogenetic analysis of amniotic fluid because of the detection of polyhydramnios, polydactyly, aortic stenosis, and the absence of vesica biliaris visualization on fetal ultrasound. Chromosome analysis was terminated with an interstitial short arm (p12-p15.1) deletion of chromosome 7 consisting of the GLI3 gene region (7p14). The presence of the short arm terminal region of the relevant chromosome was confirmed by fluorescence in situ hybridization analysis. Array comparative genomic hybridization technique verified the breakpoint regions and revealed a 17.4 Mb deletion covering the GLI3 gene. To date, reported prenatal cases with GCPS syndrome are very rare. Here we present a case of GCPS syndrome diagnosed in the prenatal period due to a de novo unbalanced chromosomal rearrangement.